2020
DOI: 10.20882/adicciones.1348
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización conductual y neuroinmune de la resiliencia al estrés social: Efectos reforzantes de la cocaína

Abstract: Numerosos estudios preclínicos han demostrado que el estrés social incrementa la vulnerabilidad a los efectos reforzantes de la cocaína. Sin embargo, los resultados obtenidos no son homogéneos, observándose siempre una subpoblación que no muestra dicho incremento. Utilizando el modelo de derrota social (DS) repetida en ratones, en este trabajo hemos querido caracterizar conductualmente a los ratones resilientes al incremento de los efectos reforzantes de la cocaína inducido por el estrés social. Utilizamos rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…In the present study, we have observed that those animals that spent more time in avoidance and flee behaviors during the last SD presented higher EtOH intake. We have obtained similar results in a previous study (Ródenas-González et al, 2020), where we observed a positive correlation between flight and avoidance behaviors and the increase in the conditioned rewarding effects of cocaine in the CPP. These results confirm that active coping and adequate adaptation to stress reduces the increase in the rewarding effects of drugs of abuse induced by social stress.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 90%
“…In the present study, we have observed that those animals that spent more time in avoidance and flee behaviors during the last SD presented higher EtOH intake. We have obtained similar results in a previous study (Ródenas-González et al, 2020), where we observed a positive correlation between flight and avoidance behaviors and the increase in the conditioned rewarding effects of cocaine in the CPP. These results confirm that active coping and adequate adaptation to stress reduces the increase in the rewarding effects of drugs of abuse induced by social stress.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 90%
“…In our experiments, cocaine produced a robust preference for the drug-paired compartment and, at a lower dose, evoked reinstatement of CPP after extinction, corroborating earlier studies (Shippenberg and Heidbreder, 1995; Ródenas-González et al ., 2021). Cocaine-induced CPP reinstatement was inhibited by JWH-133 at a dose of 10 mg/kg which abolished both chamber preference and cocaine-induced locomotor activity.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, mice that are resilient to develop anxiety when exposed to odor of a depredator exhibit changes in their dopaminergic system, suggesting a particular response of these animals to cocaine (Brodnik et al, 2017). In a previous study, we report that mice resilient to stress-induced increases in cocaine reward display less flee and avoidance behaviors during the intruder-resident encounter (Ródenas-González et al, 2020). The results of the present study confirm once again that susceptible mice adopt a passive-reactive coping profile during social defeat encounters, employing more time in flee/avoidance and submissive/defensive behaviors during the social defeat than those categorized as resilient.…”
Section: Proactive Coping Promotes Resilience While Passive-reactive mentioning
confidence: 79%
“…We have previously shown that depending on their response to cocaine-conditioned effects, there are two different populations among the defeated mice (Ródenas-González et al, 2020). In that study, we showed that three weeks after the last episode of social stress, a susceptible group of mice showed a place preference for a sub-threshold dose of cocaine as a result of an increased response to cocaine.…”
Section: Susceptibility or Resilience To Depressive-like Behaviors Anmentioning
confidence: 85%